Mars Orientation Parameters Estimation with Simulated Same Beam Interferometry - Yixiao Liu; Bo Wang; Jianguo Yan; Shangbiao Sun; Wanling Yang; Jean-Pierre Barriot (The Astronomical Journal)
The accurate determination of Mars orientation parameters (MOP) is essential for investigating the internal structure, seasonal variations of polar dry ice, and dynamic evolution of Mars. Current methods rely on Doppler and range tracking between Earth ground station and Mars lander, which are constrained by ionospheric, tropospheric and other errors. Same-beam interferometry (SBI), employing two Earth ground stations simultaneous to observe two Mars landers, effectively mitigates common-mode errors by leveraging differential phase measurements. We evaluate the accuracy enhancement of SBI in resolving MOP, key findings include: SBI with landers at lower latitudes and larger longitude difference yields higher accuracy; SBI alone is unsuitable for MOP due to its lower sensitivity to parameters compared to two-way Doppler and two-way range most of time; Combining with SBI data, two-way Doppler improves the accuracy of precession rate ( ${\dot{ψ }}_{0}$ ), obliquity rate ( ${\dot{I}}_{0}$ ), and spin rate ( ${\dot{φ }}_{0}$ ) by up to 43%, and reduced the correlation between some parameters, for certain rigid amplitudes, length-of-day (LOD) variation and polar motion parameters, there are different durations and degrees of accuracy improvement before the 700th mission day. Two-way range integrated with SBI achieves up to 45% precision gain about these three parameters, for certain rigid amplitudes and LOD variation, there are also different durations and degrees of accuracy improvement before the 600th mission day, with no significant improvement in polar motion parameters. SBI has duration selectivity and observation mode dependence for the improvement, and low-noise and low-latitude lander distribution can further extend the accuracy improvement duration.